Birth-and-Death Evolution and Reticulation of ITS Segments of Metschnikowia andauensis and Metschnikowia fructicola rDNA Repeats - Sipiczki, Matthias; Horvath, Eniko; Pfliegler, Walter P. (Frontiers in Microbiology, 2018)
The internal transcribed spacer (ITS) region (ITS1, 5.8S rDNA, ITS2) separates the genes coding for the SSU 18S and the LSU 26S genes in the rDNA units which are organised into long tandem arrays in the overwhelming majority of fungi. As members of a multigenic family, these units are subject of concerted evolution, which homogenises their sequences. Exceptions have been observed in certain groups of plants and in a few fungal species. In our previous study we described exceptionally high degree of sequence diversity in the D1/D2 domains of two pulcherrimin-producing Metschnikowia (Saccharomycotina) species which appeared to evolve by reticulation. The major goals of this study were the examination of the diversity of the ITS segments and their evolution. We show that the ITS sequences of these species are not homogenized either, differ from each other by up to 38 substitutions and indels which have dramatic effects on the predicted secondary structures of the transcripts. The high intragenomic diversity makes the D1/D2 domains and the ITS spacers unsuitable for barcoding of these species and therefore the taxonomic position of strains previously assigned to them needs revision. By analysing the genome sequence of the M. fructicola type strain, we also show that the rDNA of this species is fragmented, contains pseudogenes and thus evolves by the birth-and-death mechanism rather than by homogenisation, which is unusual in yeasts. The results of the network analysis of the sequences further indicate that the ITS regions are also involved in reticulation. M. andauensis and M. fructicola can form interspecies hybrids and their hybrids segregate, providing thus possibilities for reticulation of the rDNA repeats.